Adapting to the Pandemic: Experiences of Latin American Restaurants During COVID-19 and Potential Implications for Community Health and Food Environments. (7th June 2021) - Harrison, Elise; Rodriguez, Michelle; Veliz, Diana; Abreu-Runkel, Rosa; Fuster, Melissa
Abstract: Objectives: Assess how Latin American restaurants (LAR) have been adapting in response to COVID-19, and the potential implications of those changes for community food environments. Methods: Qualitative study design using semi-structured interviews with LAR owners and staff ( n = 12). Interviews were conducted via Zoom, lasting between 30 and 90 minutes. Verbatim transcripts were analyzed by two independent coders using Dedoose following an iterative approach for organizing results using emergent themes. Results: COVID-19 led to initial closures, decrease in clientele and interrupted food supply. LAR adjusted by switching to outdoor dining and/or delivery/takeout, reducing hours and staff, increasing social media presence, and making changes to the menus. Menus were reduced, decreasing items not well-suited for takeout/delivery, (notably salads), while keeping customer favorites, such as high-energy "comfort foods." Menu changes were more prevalent in full-service restaurants, compared with fast casual LAR. The results also include experiences with delivery companies and government assistance during COVID-19. Conclusions: The pandemic has forced drastic changes in LARs, with potential implications for future health promoting interventions. The results from this study contribute to informing how restaurants are adapting in response to COVID-19 and the potential implications on community health and nutrition, as well as what restaurants can do to prepare for future crises. This will need to be considered for the survival of the industry and the communities that they serve. Future research is needed to examine long-term effect of changes in community food environments and customers' diets. Funding Sources: NIH - National Heart, Lung, and Blood Institute